Retrospective cohort analysis of real-life decisions about end-of-life care preferences in a Southeast Asian country - Tan, Woan Shin (2019)
Objective : To describe the end-of-life care preferences of individuals, and to examine the influence of age and gender on these preferences. Design, setting and participants : A retrospective cohort study was conducted. Participants included all adults (≥21 years old) (n=3380) who had completed a statement of their preferences as part of a national Advance Care Planning (ACP) programme in Singapore. Data were extracted from the national and Tan Tock Seng Hospital ACP database. Main measures : End-of-life care preferences were obtained from the ACP document and differentiated by health status (healthy, chronically ill or diagnosed with advanced illnesses). To analyse the data, descriptive statistics and logistic regression analysis were used. Results : Across healthy and chronically ill patients, the majority did not opt for cardiopulmonary resuscitation (CPR) or other life-sustaining measures. Among individuals with advanced illnesses, 94% preferred not to attempt CPR but 69% still preferred to receive some form of active medical treatment. Approximately 40% chose to be cared for, and to die at home. Age and sex significantly predict preferences in those with advanced illnesses. Older age (>=75 years) showed higher odds for home as preferred place of care (OR 1.52; 95% CI 1.23 to 1.89) and place of death (OR 1.29; 95% CI 1.03 to 1.61) and lower odds for CPR (OR 0.31; 95% CI 0.18 to 0.54) and full treatment (OR 0.32; 95% CI 0.17 to 0.62). Being female was associated with lower odds for home as preferred place of care (OR 0.69; 95% CI 0.57 to 0.84) and place of death (OR 0.70; 95% CI 0.57 to 0.85) and higher odds for full treatment (OR 2.35; 95% CI 1.18 to 4.68). Conclusion : The majority preferred to not proceed with life-sustaining treatments, but there was still a strong preference to receive some form of limited treatment. Better understanding of end-of-life care preferences through ACP can better guide end-of-life care programme planning, and resource allocation decisions.